The Use of Tag Question in a Fairy Tale - Harahap, Beby Ariani; Padang, Serli Br; Aulia, Dian Rizka; Lubis, Yani (Pusdikra-Publishing.com, 2025)
This study examines the use of tag questions in fairy tale dialogues, specifically in the story Why Doesn’t the Rabbit Have a Long Tail?, motivated by the limited research on this linguistic phenomenon in contemporary children’s literature. The objectives are to identify the forms of tag questions, analyze their communicative functions in character interactions, and explore their impact on meaning conveyance, character development, and narrative dynamics. Employing a qualitative descriptive method with a library research approach, data were collected from the fairy tale text and supported by relevant academic sources, then analyzed pragmatically and syntactically to gain a comprehensive understanding of tag question usage. Based on the analysis of the fairy tale, it was found that the explicit use of formal tag questions is very limited, appearing only around four to five times. However, reflective questions functioning similarly are more prevalent and play a crucial role in expressing the protagonist’s inner conflict, fostering emotional engagement with readers, and reinforcing the moral message of the story. Therefore, tag questions and reflective interrogatives serve as effective linguistic strategies that enrich dialogue, enliven characters, and make the narrative more interactive and meaningful. This provides important contributions to linguistic studies in literature and benefits writers and educators in children’s literature.